Chitotriosidase Activity Is Counterproductive in a Mouse Model of Systemic Candidiasis - Schmitz, Nicholas A.; Thakare, Ritesh P.; Chung, Chun-Shiang; Lee, Chang-Min; Elias, Jack A.; Lee, Chun Geun; LeBlanc, Brian W. (Frontiers in Immunology, 2021)
Mammalian cells do not produce chitin, an insoluble polymer of N-acetyl-D-glucosamine (GlcNAc), although chitin is a structural component of the cell wall of pathogenic microorganisms such as Candida albicans. Mammalian cells, including cells of the innate immune system elaborate chitinases, including chitotriosidase (Chit1), which may play a role in the anti-fungal immune response. In the current study, using knockout mice, we determined the role of Chit1 against systemic candidiasis. Chit1-deficient mice showed significant decrease in kidney fungal burden compared to mice expressing the functional enzyme. Using in vitro anti-candidal neutrophil functional assays, the introduction of the Chit1:chitin digestion end-product, chitobiose (N-acetyl-D-glucosamine dimer, GlcNAc2), decreased fungal-induced neutrophil swarming and candida killing in vitro. Also, a role for the lectin-like binding site on the neutrophil integrin CR3 (Mac-1, CD11b/CD18) was found through physiological competitive interference by chitobiose. Furthermore, chitobiose treatment of wildtype mice during systemic candidiasis resulted in the significant increase in fungal burden in the kidney. These data suggest a counterproductive role of Chit1 in mounting an efficient anti-fungal defense against systemic candidiasis.